DNA‐Guided Assembly of Molecules, Materials, and Cells. (5th December 2019) - Yang, Donglei; Zhou, Chunyang; Gao, Fei; Wang, Pengfei; Ke, Yonggang
Abstract : DNA is the genetic blueprint for most known living organisms on Earth, but it is not merely the secret of life. Because of its programmability derived from Watson–Crick base‐pairing, DNA exhibits unparalleled versatility in constructing designer molecular structures by self‐assembly—a field called DNA nanotechnology. After decades of active pursuit, DNA has demonstrated unprecedented capability in designing highly prescribed and sophisticated artificial nanostructures, which could be either static, with well‐controlled physicochemical properties, or dynamic, with the ability to change in response to external stimuli. Researchers have devoted considerable efforts to exploring the utility of DNA nanotechnology in a variety of fields, with the majority related to harvesting their assembling power, since they are highly capable of guiding the assembly of other entities—molecules, materials, living cells, and so on—to fabricate artificial assemblies with emergent properties and functions. Herein, a brief introduction is given to self‐assembly methods in DNA nanotechnology, including DNA tiles, modular DNA bricks, and DNA origami. Four sections are then dedicated to covering the utilization of DNA nanotechnology for guided assembly of organic materials, inorganic materials, biological materials, and living cells. Lastly, DNA‐enabled molecular intelligent systems that are able to compute and execute algorithms are discussed. Abstract : DNA molecules may be programmed to self‐assemble into designer structures of physicochemical properties under unprecedented control. These molecules and structures have been demonstrated to exhibit potent capability serving as molecular ligands or templates to direct the assembly of guest entities (e.g., molecules, materials, cells) forming artificial assemblies with emergent properties and functions.